Outcome of PHILOS Plating in Proximal Humerus Fractures (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To study results of PHILOS plating in fractures of proximal humerus. Methods: The Study was conducted from first July 2011 till 31st may 2015. Twenty-nine patients having fractures ofthe proximal humerus were initially included in the study except pathological fractures and fractures in immatureskeleton. Two patients had incomplete follow up; only 27 patients had completed one year follow up in ouroutpatient department. All patients were operated using PHILOS plate for internal fixation. All patients werefollowed at 2, 6, 12(weeks), 6(months) and 1year. Oxford score and DASH) Score (Disability of arm, shoulder andhand) was used for Clinical outcome. Serial x rays were used for radiological outcome. Results: Two out of 29 patient were lost to follow up, hence 27 patients were followed for one year. There were 15male and 12 female patients whose mechanism of injury in 14 patients was road traffic accident and 13 patientsgave history of fall. All patients had radiological unions at 12 weeks except one patient who got infected. Malepatients achieved better outcome as compared to female with an average of Oxford score 30.2 (range 50-13) and anaverage DASH score 27.4 (Range 0 to 56.2) compared to 32.1(range 13t o 59) and 34 range (0 to 89.2), All the threecomplication that occurred were in female patient group. Seven patients had 2-part fracture, 11 had 3 part and 9had 4 part fractures. The 3 and 4 part fracture was more common in elderly patient above 60year age. Conclusion: PHILOS plating in fractures of proximal humerus has the best results particularly in the osteoporoticbones.Key words: PHILOS plates, proximal humerus fracture, DASH score. Oxford score